Inhibitory axons are targeted in hippocampal cell culture by anti-Caspr2 autoantibodies associated with limbic encephalitis - Pinatel, Delphine; Hivert, Bruno; Boucraut, José; Saint-Martin, Margaux; Rogemond, Véronique; Zoupi, Lida; Karagogeos, Domna; Honnorat, Jérôme; Faivre-Sarrailh, Catherine (Frontiers in Cellular Neuroscience, 2015)
Contactin-associated protein-like 2 (Caspr2), also known as CNTNAP2, is a cell adhesion molecule that clusters voltage-gated potassium channels (Kv1.1/1.2) at the juxtaparanodes of myelinated axons and may regulate axonal excitability. As a component of the Kv1 complex, Caspr2 has been identified as a target in neuromyotonia and Morvan syndrome, but also in some cases of autoimmune limbic encephalitis. How anti-Caspr2 autoimmunity is linked with the central neurological symptoms is still elusive. In the present study, using anti-Caspr2 antibodies from seven patients affected by pure limbic encephalitis, we determined that IgGs in the cerebrospinal fluid of four out seven patients were selectively directed against the N-terminal Discoïdin and LamininG1 modules of Caspr2. Using live immunolabeling of cultured hippocampal neurons, we determined that serum IgGs in all patients strongly targeted inhibitory interneurons. Caspr2 was highly detected on GAD65-positive axons that are surrounding the cell bodies and at the VGAT-positive inhibitory presynaptic contacts. Functional assays indicated that LE autoantibodies may induce alteration of Gephyrin clusters at inhibitory synaptic contacts. Next, we generated a Caspr2-Fc chimera to reveal Caspr2 receptors on hippocampal neurons localized at the somato-dendritic compartment and post-synapse. Caspr2-Fc binding was strongly increased on TAG-1-transfected neurons and conversely, Caspr2-Fc did not bind hippocampal neurons from TAG-1-deficient mice. Our data indicate that Caspr2 may participate as a cell recognition molecule in the dynamics of inhibitory networks. This study provides new insight into the potential pathogenic effect of anti-Caspr2 autoantibodies in central hyperexcitability that may be related with perturbation of inhibitory interneuron activity.